2013
DOI: 10.1142/s0219635213500222
|View full text |Cite
|
Sign up to set email alerts
|

fMRI measurement of the integrative effects of visual and chemical senses stimuli in humans

Abstract: The purpose of this study was to evaluate the integrative effects of visual stimuli with chemical senses (olfactory and gustatory) stimuli in humans. Noninvasive measurement tools such as magnetoencephalography (MEG) and functional magnetic resonance imaging (fMRI) are used to describe the mechanism of olfactory information processing in the human brain, and the neurophysiological properties of olfactory-related neurons are described. The first study analyzed the interaction between visual and olfactory stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To make research more ecological valid and to evolve a broader and more complete concept of emotional multimodality, future research should not only concentrate on audiovisual emotion processing but should also incorporate cues from other sensory channels as, e.g., olfactory ( Pause, 2012 ; Adolph et al, 2013 ), somatosensory ( Francis et al, 1999 ; Gerdes et al, 2012 ; Wieser et al, 2012a , 2014 ), or gustatory signals ( O’Doherty et al, 2001 ; Tonoike et al, 2013 ) which are also known to elicit emotional reactions and may interact with information processes of other modalities.…”
Section: Discussionmentioning
confidence: 99%
“…To make research more ecological valid and to evolve a broader and more complete concept of emotional multimodality, future research should not only concentrate on audiovisual emotion processing but should also incorporate cues from other sensory channels as, e.g., olfactory ( Pause, 2012 ; Adolph et al, 2013 ), somatosensory ( Francis et al, 1999 ; Gerdes et al, 2012 ; Wieser et al, 2012a , 2014 ), or gustatory signals ( O’Doherty et al, 2001 ; Tonoike et al, 2013 ) which are also known to elicit emotional reactions and may interact with information processes of other modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Matching an ECD model to the extracranial magnetic field became a simple and convenient method for localizing sources of cerebral activity. Experimental studies proved the accuracy of ECD localization of sources of interictal discharges (38)(39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 84%
“…Neurophysiological experiments in monkeys have shown that the olfactory nervous center and olfactory pathway project to the orbitofrontal cortex [55][56][57]. In humans, olfactory event-related potentials and magnetic fields evoked by odorant pulses synchronized with respiration are also found in the orbitofrontal area [5,6,58,59].…”
Section: The Meaning Of Simultaneous Smelling An Incense Outdoor and Putting The Hands Togethermentioning
confidence: 99%